THE SCOTTISH REFORMATION AND HOW IT DIFFERS FROM ENGLAND’S - S. J. Lamont (Концепт: философия, религия, культура, 2018)
The ways in which the Reformation began and developed in England and Scotland were distinct and led to a different type of national church in each country. The Scottish Reformation, led by John Knox, was closer to the ideas developed in Geneva by John Calvin and came to be called Presbyterian because it replaced bishops and dioceses with presbyteries composed of equal numbers of ministers and elders. The Scottish church was non-hierarchical and closer to the people than the model adopted in England. In this contribution Stewart Lamont (who has written in one of his books about the uneasy alliances which national churches have with the state) describes how the Scottish model of Reformation led to Edinburgh, the capital of Scotland, being a centre of the Enlightenment in Europe. Nowadays secularisation has overwhelmed both national churches in the United Kingdom and they have both lost their position at the centre of national life. Membership of the Kirk (the name by which the Church of Scotland is commonly known) is now less than one third of the total fifty years ago. While some evangelical churches are showing growth, the national church is now mostly composed of older members, and its moral authority over individuals has transferred to campaigning on social issues. However, the legacy of Knox and the Presbyterian system gave Scotland an educational system whose seeds started bearing fruit from the time of the Enlightenment between 1750s to 1850s when Scotland was a centre of intellectual achievement, and which is still at the heart of its educational institutions.